CONTRACTING parties to the Convention on the Prevention of Marine Pollution by Dumping of Wastes and other Matter (London Convention), 1972 : Final Act, 1996 Protocol and Resolutions. (1997)
Presents the Final Act of the Special Meeting of Contracting Parties to Consider and Adopt the 1996 Protocol to the London Convention 1972.
DC